﻿First record and characterization of Aganaspis daci (Weld, 1951) (Hymenoptera, Figitidae, Eucoilinae), a parasitoid of fruit flies, from Italy - Umberto Bernardo; Feliciana Pica; Carmela Carbone; Francesco Nugnes; Gennaro Viggiani (Journal of Hymenoptera Research, 2023)
Aganaspis daci, a larval-pupal parasitoid of several tephritid species, was unexpectedly recovered in the Campania region (Southern Italy), where it had not been intentionally released. An integrative approach was used to conduct a comprehensive characterization of this parasitoid, confirming its identification through a comparison with specimens obtained from laboratory rearing. While A. daci emerged from puparia of Ceratitis capitata during this study, its original association was recorded with Bactrocera dorsalis. The presence of A. daci in Italy highlights its successful establishment, possibly facilitated by the recent invasive process of its host, B. dorsalis, offering promising prospects for future tephritids control strategies. It is intriguing to note that the mt-haplotypes found in Italy were only partially shared with those observed in specimens originating from a Spanish rearing, suggesting likely distinct origins for at least part of the Italian population.